Quick algebra review : a self-teaching guide, second edition - Selby, Peter H.; Slavin, Steve ([S.l.] : John Wiley & Sons, 1993)
The fastest, easiest way to brush up on your algebra! Quick Algebra Review Need to hone your algebra skills? This bestselling review course in intermediate algebra gives you all the concepts, procedures, and problem-solving methods you need to succeed. * Each chapter begins with an easy-to-use chart that zeroes in on your problem areas. Now you can avoid wasting hours rehashing familiar concepts. * Every key algebraic concept is covered thoroughly--including positive and negative numbers, fractions, rational numbers, factoring, linear equations, quadratic equations, and word problems. * Hundreds of questions, answers, review problems, and quizzes help you to test your progress every step of the way. Now updated and revised to be even more relevant and accessible than ever, Quick Algebra Review is packed with practical examples drawn from real-life situations. Cover Design: Donald Munson.